2013
DOI: 10.1155/2013/730829
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy for the Treatment of the Open Abdomen and Incidence of Enteral Fistulas: A Retrospective Bicentre Analysis

Abstract: Introduction. The open abdomen (OA) is often associated with complications. It has been hypothesized that negative pressure wound therapy (NPWT) in the treatment of OA may provoke enteral fistulas. Therefore, we analyzed patients with OA and NPWT with special regard to the occurrence of intestinal fistulas. Methods. The present study included all consecutive patients with OA treated with NWPT from April 2010 to August 2011 in two hospitals. Patients' demographics, indications for OA, risk factors, complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
2
22
0
3
Order By: Relevance
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…While there is experimental evidence of at least one benefit to the use of irrigation in trauma victims [39], our results strongly suggest an upper limit of 5L for the effluent. This has relevance for today's practice, since epidemiological evidence exist for the current use of Intraoperative Peritoneal Lavage for this indication in surgical practice [41][42][43][44][45][46][47][48][49][50]. Our trial has several limitations: Since damage control techniques were utilized when indicated (as per the contemporary accepted standard of care) it is very possible that the potential benefits and/or harms (or lack thereof) that the intervention has in this population remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the type of cycle of negative pressure therapy, we surprisingly found that the spontaneous closure rate was 70% (7 of 10 EAFs) using intermittent settings of negative pressure, whereas in the group of patients treated with continuous pressure, 57% of EAFs closed spontaneously (12 of 21 EAFs). The mean number of NPWT dressing was 9 (SD 3⋅3; range [4][5][6][7][8][9][10][11][12][13][14][15][16]. Three patients died (18⋅8%) during NPWT in OA management.…”
Section: Resultsmentioning
confidence: 99%
“…Однако количество пациентов, которым была применена методика Виттманна, было существенно ниже, чем при использовании прочих методик. Внутрибрюшные осложнения (абсцессы) -достоверно ниже при использовании вакуум-терапии (7,7 % -перитонит и 1,4 % -травма), кишечные свищи при использовании методики Виттманна -2,8 % [56].…”
unclassified
“…Применение трансабдоминальных швов в сочетании с трубками или пуговицами, через которые проводятся наружная часть нитей, способствует уменьшению диастаза краев, однако длительное их применение также связано с определенными неудобствами в виде некрозов кожи в месте прилегания наружных частей, с прорезыванием швов. Частично эти проблемы решаются применением систем динамического сведения краев раны -ABRA-system [4,56].…”
unclassified